The Influence of Parenting Style on the Character of Discipline, Responsibility, and Respect for Middle Childhood Age Children (Universitas Negeri Semarang, 2021)
The aim of this research is to see the effect of parenting style on discipline, responbility, and respect in middle childhood. The subjects are children aged 8 and 9. Characters and parenting style of the subjects are measured by instruments that were constructed by a group of character Education Research. Based on the measurement using one-way Anova. The result shows that there are significant diffrences between characters, which are discipline, Responbility, and respect, and parenting styles, which are authoritative, authoritarian, permissive, and neglectful in middle childhood.